The Archive of Oppressed Literature in the German Democratic Republic. Issue 1 (January 2018) - Buchholz, Matthias
Abstract : The "Archive of Oppressed Literature in the GDR" (AOL) is a project funded by the Federal Foundation for the Study of Communist Dictatorship in East Germany for the purpose of research into works of literature produced in the Soviet Occupation Zone or the German Democratic Republic (GDR) which have hitherto remained unknown because they were subject to total or partial censorship. Literature in the GDR was more diverse and ambiguous than the texts published contemporaneously suggest. Given what is known about the GDR's censorship practices and political constraints this is unlikely to cause astonishment. Yet unpublished literary manuscripts portraying an image of the state and society other than the officially propagated one failed to reach the general public even after 1989. The AOL aims to foster a broader and more cogent appraisal of literary production in the GDR. It provides hitherto completely unknown material that serves both to complement and provide a revision of the literary canon as it was defined by GDR official literary criticism and, frequently, than that also indiscriminately adopted in the West. A further important aim of the project is to morally rehabilitate authors who were spurned in the GDR and to bring their work, which had no chance of being published when first written, to public attention today. The review to date of these unpublished works reveals that the driving force for their suppression was the politically motivated elimination of the literary voices of those individuals who were not prepared to accept the restrictions imposed on their freedom by the cultural policy of the day.